The Difference of Asphyxia Neonatorum Incident between Very Preterm Labor That Is Followed or Not by Premature Rupture of Membranes at RSD dr. Soebandi of Jember - Nely Masruroh; Yonas Hadisubroto; Rena Normasari (Faculty of Medicine, University of Jember, 2018)
Asphyxia neonatorum is an infant's inability to breathe spontaneously and regularly soon after birth. Risk factors of neonatal asphyxia are preterm labor and premature rupture of membranes. In the poor and developing countries there are many occurrences of asphyxia at gestation less than 32 weeks (very preterm). The aim of this study is to describe the incidence of asphyxia neonatorum in very preterm labor followed by premature rupture of membranes, describes the incidence of asphyxia neonatorum in very preterm labor that is not followed by premature rupture of membranes, and the difference of asphyxia neonatorum incident between very preterm labor that is followed or not by premature rupture of membranes. The type of this research was retrospective analytical observational with cross sectional approach and total sampling technique. The population was a single preterm delivery mother with spontaneous presentation of heads born in RSD dr. Soebandi from January 2015 - January 2017. From 465 mothers, 65 mothers meet the inclusion criteria. Data is processed and presented in the form of frequency distribution table then analyzed using Chi-Square test. The results showed that mothers with very preterm followed by premature rupture of membranes did not have asphyxia (22 mothers or 33.8%) and mothers with very preterm that is not followed by premature rupture of membranes did not have asphyxia (18 mothers or 27.2%). Based on Chi-Square statistical test results obtained p-value (0.298)> α (0.05) and it can be concluded that is statistically at 95% confidence level there is no significant difference in the incident of asphyxia neonatorum between very preterm labor that is followed or not by premature rupture of membranes in RSD dr. Soebandi Kabupaten Jember.Keywords: Asphyxia neonatorum, preterm labor, premature rupture of membranes